Kinetic energy measurements of ions emitted from alkali halides and their mixtures in 252Cf plasma desorption mass spectrometry - Abeywarna, U.K.; Zubarev, R.A.; Hakansson, P.; Ariyaratne, T.R. (University of Peradeniya. Peradeniya, 1997)
Kinetic energy measurements of both positive and negative ions emitted from several alkali halides and their mixtures are reported. The measurements were conducted using the energy cut-off property of the ion mirror of a reflector type 252Cf plasma desorption mass spectrometer. The results obtained indicate that some fraction of the desorbed ions emitted under 252Cf bombardment have a kinetic energy deficit compared to die ions which gain full kinetic energy during the acceleration-region. The initial kinetic energy of a particular ion was found to be rather independent upon the sample composition.
Keywords: Physics; Kinetic energy measurements; Alkali halides ions; 252Cf plasma desorption mass spectrometry; Ion physics